2008
DOI: 10.1007/s10800-008-9553-z
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the electrodeposition process for CoPt alloy formation

Abstract: The stability of the process for electrodeposition of CoPt alloys from ammonium citrate electrolytes containing [Pt(NO 2 ) 2 (NH 3 ) 2 ] 0 as the source of Pt was studied. Voltammetric monitoring of the anodic oxidation of the electrolyte and deposition of CoPt on the cathode showed the effect of the changes of the nature of the Pt complex on the performance of the plating bath. Anodic oxidation of the Pt complex was shown to involve mainly the oxidation of NO À 2 and to some extent NH 3 ligands. The cathodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…It should be noted that during this pretreatment the pH changes to 6. This peak is associated with oxidation 2 NO − and its disappearance is associated with the replacement of this ligand from the Pt-containing complex by water molecules or citrate ions, as shown in our earlier publication (10). No peak related to Table I).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…It should be noted that during this pretreatment the pH changes to 6. This peak is associated with oxidation 2 NO − and its disappearance is associated with the replacement of this ligand from the Pt-containing complex by water molecules or citrate ions, as shown in our earlier publication (10). No peak related to Table I).…”
Section: Resultssupporting
confidence: 60%
“…Additionally, more intensive hydrogen evolution from ammonium ions on the electrodes with higher Pt contents can contribute to this correlation. Earlier it was shown that hydrogen evolution can proceed as a result of 4 NH + ions reaction on Pt cathode (10,16). Fig.…”
Section: Nh In Solutionmentioning
confidence: 93%
See 2 more Smart Citations
“…According to several works on CoPt electrodeposition, hard-magnetic properties are easierly achieved in the as-deposited state when the alloy is plated from alkaline baths above room temperature, typically at 50-60 ºC. [29][30][31] Under these conditions, Co-rich alloys with hexagonal close-packed phase are frequently obtained. Unfortunately, AAO cannot tolerate pH values beyond 8.2 (at room temperature) and undergoes dissolution in the electroplating bath, [32] which is even exacerbated at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%